The perception and resilience of Bagang community on climate change in Marine Protected Area, Pitas, Sabah, Malaysia - Jurry Foo @ Jurry F. Michael; Marja Azlima Omar; Diana Demiyah Mohd Hamdan; Oliver Valentine Eboy (Akademi Sains Malaysia, 2022)
Climate change had caused occurrence of more frequent big El Nino and La Nino phenomenon that led to drought and flood disasters onto coastal communities and affecting their quality of life. This study aims to ascertain the perceptions of the coastal community of Kampung Mempakad Laut, Pitas, Sabah, Malaysia which is in the boundary of Tun Mustapha Park on climate change. Data is collected through in-depth interviews with the Bagang community and the data was analysed by descriptive methods. The Bagang community members have knowledge and is aware of the changes in the climate conditions through the happenings of extreme event orchestrated by mother nature that relates to the change in climate phenomena despite not knowing or not familiar with the wellused terms ‘climate change’. Examples of those extreme events are major floods, changes in dry and wet seasons, as well as long unpredictable dry season. They perceive those events as pressure that ultimately threatens their safety and affects Bagang activities. However, they have come up with their own strategies in adapting to the phenomena including precautionary and preparatory measures for enduring natural disasters, modifications of dwelling houses, attempts to increase understanding and cognisance of the changes in environmental surroundings enabling them to come up with better predictions. The experience and resilience of Bagang community that had endured extreme events related to climate change had provided further insights in understanding human’s adaptations to climate change and could become useful guidelines to other coastline communities at large.